Analysis of the Suitability of Irrigation Water Quality in the Data Makmur Secondary Canal for Agricultural Crops Based on the SAR and RSC Method Classification - Rifa Raihan; Syahrul; Purwana Satriyo (Balai Besar Standardisasi dan Pelayanan Jasa Pencegahan Pencemaran Industri, 2026)
This study aims to analyze the suitability of irrigation water quality in the Data Makmur Secondary Canal for agricultural crops based on the SAR and RSC method classifications. This study uses a quantitative approach supported by laboratory analysis. Water sampling was carried out with reference to the Indonesian National Standard (SNI) 06-2412-1991 concerning Water Quality Sampling Methods. Irrigation water samples were taken at the observation points of the Data Makmur Secondary Canal, with each sample volume ranging from 200–500 mL. The water samples were then analyzed at the Banda Aceh Industrial Standardization and Services Center and the Environmental Quality Testing Engineering Laboratory of the Chemical Engineering Study Program, Faculty of Engineering, Syiah Kuala University. The results of the irrigation water quality analysis in the Data Makmur Secondary Canal showed that the Sodium Adsorption Ratio (SAR) value for all samples was in the range of 0.3547–0.4471. This value is included in the very good category according to Todd standards (<10 meq/L), thus indicating that the irrigation water does not have the potential to cause sodicity problems and is still safe to use for agricultural activities. However, the Residual Sodium Carbonate (RSC) value showed a relatively high range, namely 1.927–3.629 meq/L. Based on Eaton's classification (>2.50 mEq/L), most samples are classified as unsuitable for irrigation, except for several points in Sample 2. This condition indicates the potential risk of soil structure degradation must be more closely aligned with the material being extracted and decreased soil permeability if water is used continuously. Therefore, regular water quality monitoring and further studies are needed with additional parameters and sampling points to achieve a more comprehensive representation of irrigation water quality.